Reliability-based optimal next inspection time of prestressed concrete bridges including the effect of corrosion deterioration. - De León, David; Díaz Camacho, Sergio; González Pérez, Carlos Alberto (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Â  As the traffic demands grow constantly, and some vehicle bridges deteriorate due to corrosion, bridge agencies require non expensive procedures to support decisions on cost-effective maintenance schedules. In this paper a reliability-based formulation is proposed for the prediction of the next inspection time including the corrosion deterioration and the epistemic uncertainty on the corrosion initiation time. For the identification of the bridge integrity state, where little or no follow up has been previously made, the prediction contains a great deal of epistemic uncertainty. The impact of this uncertainty on the bridge failure probability is appraised. The bridge reliability is calculated by comparing the bridge maximum moment with the bridge capacity which depends on the corrosion on the bridge beams. The bridge failure probability is compared with the acceptable failure probability which is used as the safety threshold and it is calculated from the minimization of the annual expected life-cycle cost. Finally, epistemic uncertainty is introduced in the corrosion initiation time and the optimal next inspection time is obtained.